Eco-design of portable solar-powered telescopic lamp for off-grid areas in Indonesia - Kadek Heri Sanjaya; Ahmad Rajani; Hendri Maja Saputra; Dalmasius Ganjar Subagio; Ridwan Arief Subekti; Ahmad Fudholi (Institute of Advanced Engineering and Science, 2021)
This study describes the development of eco-design of portable solar-powered telescopic lamp for off-grid area in Indonesia. Several design requirements for the lamp, namely, sustainability, portability, affordability, and reliability, are the objectives of the design process in this study. Sustainability is achieved through renewable energy and the application of eco-design principles. Portability means it is lightweight, compact and can be carried anywhere inside a tube. This solar-powered telescopic lamp was designed with a 3.7 V, 15.6 Ah battery power specification such that the battery power is around 57.72 Wh. The optimal use of the battery is 80% of the total battery power that is 46.176 Wh. With a power of 46,176 Wh, the battery can turn on the LED strip light with a 4.8 W power specification for 9.62 h. The test results showed that the telescopic lamp endurance met the expected specifications. The real consumed power by the LED strips was around 1.9 W. The charging test using solar panels with 12 Wp specifications showed that it will be fully charged in around 3.8 h. However, the performance of the telescopic lamp, especially in the charging process, is affected by the environment condition, such as sunlight intensity, ambient temperature, and humidity.